Uji Jalan Enam Menit Sebagai Indikator Prognosis Pada Pasien CHF Kronik Stabil Pada Rehabilitasi Jantung Fase II - Deddy Tedjasukmana Basuni; Fitria Fitria (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Intorduction: Congestive heart failure is a complex clinical syndrome that may result from disturbances in myocardial function (systolic and diastolic function) leading to decreased perfusion of cardiac blood flow. The main goals in treating patients with heart failure are to improve functional capacity and quality of life, as well as to reduce mortality and morbidity. Cardiac rehabilitation is one of many forms of treatment recommended by the American Heart Association and has been proven safe and effective in patients with heart failure. Case: This case report consists of three patients undergoing phase two cardiac rehabilitation. Case Discussion: Each patient underwent several examinations consisting of recollection of previous medical history and current complaints. Vital signs and Borg Scale were checked before and after the walking test. The 6-Minute Walk Test was carried out according to the standard protocol on a 30-meter flat track. Conclusion: From a series of 6-minute walking trials conducted on three patients, there was a significant increase in mileage since cardiac rehabilitation phase I, early phase II, and four weeks of phase II exercise.